Multiobjective optimization in the Airport Gate Assignment Problem, exact versus evolutionary multiobjective optimization - Kaliszewski, Ignacy; Miroforidis, Janusz; Stańczak, Jarosław Tomasz (Computer Science, 2017)
In this paper, we approach the Airport Gate Assignment Problem by Multiobjective Optimization as well as Evolutionary Multi-objective Optimization. We solve a bi-criteria formulation of this problem by the commercial mixedinteger programming solver CPLEX and a dedicated Evolutionary Multiobjective Optimization algorithm. To deal with multiple objectives, we apply a methodology that we developed earlier to capture decision-maker preferences in multi-objective environments. We present the results of numerical tests for these two approaches.